The role of surgery in refractory epilepsy secondary to polymicrogyria in the pediatric population. (11th September 2018) - Jalloh, Ibrahim; Cho, Newton; Nga, Vincent D.W.; Whitney, Robyn; Jain, Puneet; Al‐Mehmadi, Sameer; Yau, Ivanna; Okura, Hidehiro; Widjaja, Elysa; Otsubo, Hiroshi; Ochi, Ayako; Donner, Elizabeth; et al.
Summary: Objective: Polymicrogyria (PMG) is a common malformation of cortical development. Many patients with PMG will have medically refractory epilepsy but the role of epilepsy surgery is unclear. The objective of this study was to assess the efficacy of surgical resection/disconnection in achieving seizure control in pediatric patients with PMG. Methods: A retrospective review of children undergoing epilepsy surgery for PMG between 2002 and 2017 at The Hospital for Sick Children in Toronto, Canada, was performed. Results: A total of 12 children aged 6 months to 17.8 years (median 8.8 years) underwent resective surgery (7 children) or functional hemispherectomy (5 children). Gross total resection or complete disconnection of PMG was carried out in 7 of 12 children. Follow‐up duration was between 1 and 9 years (median 2.1 years). Nine children remained seizure‐free at last follow‐up. Complete resection or disconnection of PMG led to seizure freedom in 6 of 7 patients (86%), whereas subtotal resection produced seizure freedom in 3 of 5 patients (60%). Significance: We present one of the largest surgical series of pediatric PMG patients. Seizure outcomes were best with complete resection/disconnection of PMG. However, tailored resections based on electroclinical and neuroradiologic data can produce good outcomes and remain an appropriate strategy for patients with extensive PMG.